Recent Advances in Nanotheranostic Agents for Tumor Microenvironment–Responsive Magnetic Resonance Imaging - Jin, Longhai; Yang, Chenyi; Wang, Jianqiu; Li, Jiannan; Xu, Nannan (Frontiers in Pharmacology, 2022)
Nanomaterials integrating a variety of excellent properties (such as controllable/suitable size, surface modifier and multifunctionality) have attracted increasing attentions in biomedical field and have been considered as new generation of magnetic resonance imaging (MRI) contrast agents (CAs). In recent years, stimuli-responsive nanomaterials with specifically responsive ability have been synthesized as MRI CAs, which can significantly improve the diagnostic sensitivity and accuracy depending on their outstanding performance. In addition, the inherent tumor microenvironment (TME) of malignant tumor is considered to possess several unique features such as low extracellular pH, redox condition, hypoxia, and high interstitial pressure, that are significantly different from healthy tissues. Hence, constructing nanomaterials for TME-responsive MRI as an emerging strategy is expected to overcome the current obstacles for precise diagnosis. This review focuses on recent advances of nanomaterials in their application of TME-responsive MRI that trigger the diagnostic function in response to various endogenous stimulation, including pH, redox, enzyme and hypoxia. Moreover, the future challenges and trends in the development of nanomaterials serving as TME-responsive MRI CAs are discussed.